2013
DOI: 10.1155/2013/260830
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Single- and Double-Averaged Second-Order Models to Evaluate Third-Body Perturbation Considering Elliptic Orbits for the Perturbing Body

Abstract: The equations for the variations of the Keplerian elements of the orbit of a spacecraft perturbed by a third body are developed using a single average over the motion of the spacecraft, considering an elliptic orbit for the disturbing body. A comparison is made between this approach and the more used double averaged technique, as well as with the full elliptic restricted three-body problem. The disturbing function is expanded in Legendre polynomials up to the second order in both cases. The equations of motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…The double averaged model is a little bit faster in those reductions. This fact is also observed in Domingos et al [ 37 ], which studied this problem considering an elliptic orbit for the disturbing body but considering the expansions only up to the second order.…”
Section: The Critical Inclination Problemsupporting
confidence: 68%
“…The double averaged model is a little bit faster in those reductions. This fact is also observed in Domingos et al [ 37 ], which studied this problem considering an elliptic orbit for the disturbing body but considering the expansions only up to the second order.…”
Section: The Critical Inclination Problemsupporting
confidence: 68%
“…Different initial eccentricities (0.0, 0.05, 0.10, 0.15 and 0.20) are considered for the orbit of the moon, which means that, in a system fixed in the moon, those are the eccentricities of the disturbing body, the planet. Those choices are made based on Domingos et al (2013Domingos et al ( , 2014, which showed that averaged models have good accuracy up to those values. The system used as an example for the present studies has the same physical data (masses and distances) of the Earth-Moon system, but considers possible eccentricities for the orbit of the secondary body around the primary.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…By substituting Eq. (1) into the Lagrange's planetary equations, the variation of the orbital elements is given by Domingos et al (2013a):…”
Section: Dynamical Modelmentioning
confidence: 99%
“…To remove the short-period oscillations and any dependence on the position of the thirdbody r , the single-averaged disturbing potential is averaged again, now with respect to the third-body's period (Domingos et al 2013a):…”
Section: Dynamical Modelmentioning
confidence: 99%